STUDY OF COAL SIZE EFFECT FROM 44 mikron TO 230 mikron FOR SPONTANEOUS COMBUSTION POTENTIAL USING ADIABATIC HEATING LABORATORY SCALE EQUIPMENT - Insani - Nim: 12114058 , Trisna
Spontaneous combustion of coal is one of the serious problems for mining activities in open pit mining or underground mining as it can cause potentially large fires. Guney, 1968, categorizing the causes of spontaneous combustion of coal into intrinsic factors and extrinsic factors. Intrinsic factors include pyrite, moisture, particle size, etc, whereas extrinsic factors include O2 concentration, temperature, geological conditions, etc. In this study, it will be focused on particle size (intrinsic factor) as a factor influencing spontaneous combustion of coal which is using adiabatic oxidation method with oxygen gas flow of 0.05 L / min on the test tube and data retrieval done twice to see the differences that may occur. The grain size used is -65 + 100 #, -100 + 200 #, and -200 + 325 #. The results from this research is R70 value and activation energy, and R70 value in experiment I and II ranging from -200 + 325 #, -100 + 200 #, and -65 + 100 # is 37.93 0C / hour; 23.51 0C / hour; 12.68 0C / hour. While the activation energy values in experiment I and II ranging from -200 + 325 #, -100 + 200 #, and -65 + 100 # is 18,133.7 J / mol; 25,703.8 J / mol; 12,388.7 J / mol. If the coal size is smaller, the R70 value is getting increase and the activation energy value indicates an ascending trend.